Neuroradiology in Clinical Practice - Rana, Abdul Qayyum. (Springer International Publishing : Imprint: Springer, 2013)
This quick reference guide for medical students and residents presents over sixty clinical case studiesofmajor neurological conditions and their associated neuroimaging characteristics. A primer on thefundamental physics which underlie neuroimaging techniques is also provided. The content is organized by pathology type and the structure of every topic is similar to help the reader develop his or her thinking process in a stepwise fashion and to provide a rational approach to imaging interpretation. Neuroradiology in Clinical Practice is aimed at medical students and residents doing their rotations in neurology, internal medicine, emergency medicine, and family medicine, but will also be useful for allied health professionals, nurse practitioners, physician assistants and other primary medical care providers.